Eficiencia: el código genético de la gestión - Macera, Danilo (2018)
This essay analyses the relationship between efficiency, efficacy, and effectivity. While the first two concepts refer to resources and objectives, respectively, the third one is related to the combination of both concepts. Efficiency is a concept present in nature, specifically in the animal kingdom. This essay presents success cases of companies that have archived efficiency; and identifies three capabilities that any organization must develop to reach efficiency, these being the optimal estimation of production quantity of good and services; identification of strategic resources and their management; and, finally, the determination of objectives with clarity.